Charge transfer in thin films of donor-acceptor complexes studied by infrared spectroscopy - Nanova, Diana; Beck, Sebastian; Glaser, Tobias; Pucci, Annemarie (Organic electronics, 2012)
The degree of charge transfer in thin films of organic charge transfer (CT)-complexes, which are deposited via thermal evaporation, is examined via infrared-spectroscopy. We demonstrate a linear relationship between the shift in the excitation energy of the CN-stretching mode of CT-complexes with the acceptor 7,7,8,8-tetracyanoquinodimethane (TCNQ) and the charge transfer. The measured correlation corresponds very well with DFT calculations. For Na-TCNQ we observe a splitting in the peak of the CN-stretching mode, which can be explained by the coupling of two modes and was confirmed by the calculations. In CT-complexes with partial charge transfer the appearance of an electronic excitation is demonstrated.
Gesehen am 30.10.2018